Cleanliness of Canal Walls following Gutta-Percha Removal with Hand Files, RaCe and RaCe plus XP-Endo Finisher Instruments: A Photographic in Vitro Analysis - Karamifar, Kasra; Mehrasa, Neda; Pardis, Pouyan; Saghiri, Mohammad Ali (Iranian Endodontic Journal, 2017)
Introduction: Gutta-percha must be removed from the root canal space during retreatment to ensure a more favorable outcome. The aim of this study was to compare the efficacy of hand instruments, RaCe and RaCe plus XP-endo finisher instruments in removal of gutta-percha from root canal walls during retreatment. Methods and Materials: Thirty single-rooted premolars were prepared, obturated, and divided into three groups according to retreatment method; in group 1, retreatment was carried out by hand instruments, while in groups 2 and 3 retreatment was done using RaCe rotary files alone or accompanied by XP-endo finisher instruments, respectively. After retreatment, teeth were sectioned longitudinally and photographic images were taken. The amount of remaining gutta-percha in coronal, middle and apical thirds was quantified using Image J software. The two-way ANOVA and post hoc Tukey’s tests were used to analyze data. The level of significance was set at 0.05. Results: RaCe cleaned the apical third significantly better than hand instrumentation. In the coronal third, RaCe+XP-endo finisher was more effective than RaCe. RaCe+XP-endo finisher was more effective than hand instrumentation in the entire root canal. The amount of remaining gutta-percha was the least in the apical part and increased toward the coronal part with the use of XP-endo finisher (P<0.05). Conclusion: Rotary instrumentation was more effective in removing gutta-percha from the canal walls. Furthermore, use of XP-endo finisher file resulted in cleaner canal walls and was more effective in removing gutta-percha from the coronal toward the apical part of the canal. Keywords: Gutta-Percha Removal; RaCe; Root Canal Retreatment; XP-endo Finisher